METAMORPHOSIS INTEGRASI THEOLOGI ISLAM DENGAN SPIRIT WIRAUSAHA - Elvia Zahra, Anzu; Mustaniruddin, Ahmad; Sobur, Kadir; Kusnadi, Edy; Mesalina, Juliana (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
This research is initiated by the economic contestation in both the Islamic and Western worlds. In the context of Islamic theology, there are several views which say that success is dependent on human’s effort and God's will. The purpose of this research is to explore the concept of entrepreneurial motivation that carried out by the Qolbu Management (QM), Emotional Spiritual Quotion (ESQ) and The Pattern of Allah's Help (PAH). It’s a qualitative approach. The source of data in this research are by analyzing books, videos, audio visuals such as Youtube, then by studying literature (library research). Scientific interviews will also be conducted with several individuals (academics and practitioners) as supporters of the distinction of Islamic theology with an entrepreneurial spirit. The findings were motivated by the emergence of the concept Qolbu Management, ESQ and PAH which is one of the efforts to integrate the teachings of Theological Tauhid into the concept of Islamic entrepreneurship. The similarities between the concepts of Qolbu Management, ESQ and PPA are Theological Tauhid. While the differences are the Qolbu Management Concept is closer to Asy Ariyah theology, ESQ is closer to the Mu'azilah theology concept, while PAH is more identical to the Jabariyah concept. The point of the concept of entrepreneurship, monotheism and the concept entrepreneurial of Qalbu Management, ESQ and PAH, namely: Guiding towards the maximum monotheism and teaching humans to try with their potentials and do not forget to surrender to Allah SWT Penelitian ini diawali dengan kontestasi perekonomian baik di dunia Islam maupun Barat. Dalam konteks teologi Islam ada beberapa pandangan yang mengatakan bahwa kesuksesan adalah tergantung dari usaha manusia dan kehendak Tuhan. Tujuan dari penelitian ini yaitu untuk mendalami konsep motivasi wirausaha yang dilakukan oleh Manajemen Qalbu (MQ), Emotional Spritual Quotion (ESQ) dan Pola Pertolongan Allah (PPA). Penelitian ini menggunakan pendekatan kualitatif. Sumber data dalam penelitian ini adalah dengan menganalisis buku-buku, video-video, audio visual seperti Youtube, kemudian dengan studi literatur (library research). Wawancara ilmiah juga akan dilakukan dengan beberapa individu (akademisi dan praktisi) sebagai pendukung distingsi ilmu teologi Islam dengan spirit wirausaha. Hasil temuan dalam penelitian ini dilatarbelakangi oleh munculnya konsep Manajemen Qolbu, ESQ dan PPA yang merupakan salah satu usaha untuk mengintegrasikan ajaran-ajaran Tauhid Teologis kedalam konsep wirausaha secara islami. Adapun persamaan dari konsep Manajemen Qolbu, ESQ dan PPA yaitu Tauhid Teologis. Sedangkan perbedaannya Konsep Manajemen Qolbu Lebih mendekati teologi Asy Ariyah, ESQ mendekati Konsep teologi Mu’tazilah sedangkan PPA lebih identik dengan konsep Jabariyah. Titik temu konsep kewirausahaan dan ketaudhid dan konsep wirausaha manajemen Qalbu, ESQ dan PPA yakni : Membimbing terhadap ketauhidan yang maksimal dan mengajarkan manusia untuk berusaha dengan potensi yang dimiliki dan kemudian tidak lupa akan berpasrah diri kepada Allah SWT